Paper 45: Preoperative MRI Offers Minimal Clinical Utility, Delays Access to Hip Arthroscopy, and Lacks Cost-Effectiveness in Patients Aged 40 or Under with Classic Femoroacetabular Impingement Syndrome: A Retrospective 5-Year Analysis. Issue 7 (30th July 2022) - Helm, J. Matthew; Berrier, Ava; Vega, Jose; Yalçin, Sercan; Kunze, Kyle; Harris, Joshua; Feingold, Jake; Ramkumar, Prem
Objectives: Background: The volume of hip arthroscopy for femoroacetabular impingement syndrome(FAIS) has dramatically risen, and data increasingly supports early intervention from symptom onset. In an increasingly value-conscious environment, the practice of routinely acquiring preoperative MRIs for primary hip arthroscopy patients in the setting of FAIS defined by concordant history, physical exam, and radiographs may offer questionable clinical utility, waste healthcare resources, and negatively impact patient outcomes by delaying access to care. Hypothesis/Purpose: The primary purpose of the present study was to determine whether preoperative MRI provided clinical utility for patients aged 40 or under with FAIS undergoing primary hip arthroscopy. A secondary purpose was to quantify the delay in care due to ordering the preoperative MRI. Methods: A cohort of 1, 786 consecutive patients who underwent hip arthroscopy between August 27, 2015, and December 31, 2020, were reviewed from the practice of a single fellowship-trained hip arthroscopist at a quaternary referral center. Our inclusion criteria were as follows: primary hip arthroscopy for FAIS and age 40 years or under. Patients were excluded if they presented to the office already with an MRI, had a contraindication to undergo MRI, elected to reattempt a second round of conservative management, or underwent a concomitant periacetabular osteotomy. The interpretation of the preoperative MRI was subsequently compared to the in-office evaluation, consisting of history, physical exam, and plain radiographs, as well as the intraoperative findings at the time of hip arthroscopy to assess for agreement. In addition to baseline demographic data, time from initial office evaluation to MRI completion and time from MRI to hip arthroscopy were recorded. Results: A total of 198 patients met the criteria for evaluation, 70% of which were female. Mean BMI and age were 25.6 and 24.8, respectively. All 198 patients had MRI findings demonstrating anterosuperior labral tears that were again re-demonstrated and repaired intraoperatively during hip arthroscopy. Of the three patients with questionable articular cartilage pathology noted on MRI, none required surgical treatment or reoperations to address cartilage pathology. No patients underwent primary labral reconstruction. The mean time from in-office FAIS diagnosis to noncontrast MRI acquisition was 15.0 days. The mean time from MRI to hip arthroscopy was 73.0 days. Conclusions: Preoperative MRI for patients with FAIS aged 40 or under undergoing primary hip arthroscopy provides little to no actionable clinical information with respect to the labrum or cartilage and may in turn negatively impact outcomes by delaying access to care unnecessarily by at least two weeks. Whether driven by practice dogma from referring physicians or arbitrary insurance preauthorization standards, the necessity of routine preoperative MRI in the young hip population with FAIS indicated for primary hip arthroscopy should be challenged by all relevant stakeholders from both clinical and value-based perspectives. FAIS. Time from initial visit to MRI and MRI to procedure. Table 1. Demographic data for cohort of included patients